PERANAN MULSA DALAM MENINGKATKAN PERTUMBUHAN DAN PRODUKSI CABAI MELALUI MODIFIKASI KONDISI FISIK DI DALAM TANAH - Joko Basuki; Ahmad Yunus; Edi Purwanto (Politeknik Pertanian Negeri Kupang, 2009)
Soil is growing media for plant growth. It preserves water and nutrients for plants. The physical changes in soil affect the life of roots and plant performances. The goal of research was to change physical condition in soil through mulching for increasing pepper plant production. Land for pepper cultivation was mulched using rice straws and plastic sheet (PE). Physical condition such as soil suhue and humidity and content of organic matters in the soil were measured or examined. Also, production components such as plant height and stalk diameter were measured as well as fruit production. The result showed that mulching increased significantly soil suhue and humidity as well as content of organic matters in the soil. Mulching increased plat height, diameter of stalk, and fruit production, especially in using rice straws Therefore, mulching have a role in increasing growth and production pepper fruit through modification of physical condition in soil.Keywords : mulching, growth, production, pepper